Designing Asymptotic Geodesic Hybrid Gridshells. (November 2022) - Schling, Eike; Wang, Hui; Hoyer, Sebastian; Pottmann, Helmut
Abstract: Fabrication and assembly of freeform shells can be simplified significantly when controlling the curvature of structural elements during the design phase. This approach has produced fundamental insights to bending-active construction, using the elastic property of elements to form efficient load-bearing structures. This paper is focused on gridshells that are built from straight and flat slats. The slats are combined in two orientations, tangential and normal to the design surface, to create robust and versatile triangulated grids. For this purpose, we generate hybrid webs of asymptotic and geodesic paths on freeform surfaces. The research combines geometric computing with architectural building practice. We present a computational workflow for the design and interactive modification of hybrid asymptotic geodesic webs. At its core are discrete models that are based on concepts of differential geometry and allow to compute constrained structures within an optimization framework. The resulting webs are tested for architectural applications. We derive a strategy for the elastic erection process, in which geodesic lamellas are used as a guide and bracing of the spatial structure. Two architectural scenarios, a timber roof and a steel facade are presented. Their feasibility for construction is verified through prototypical joints and physical models. The research introduces a new class of networks and related surfaces and offers insights into the practical challenges of freeform construction from elastic slats. Graphical abstract: Highlights: Introduction of new triangular hybrid webs combining asymptotic and geodesic (AG) curves. Computational method to design and modify optimized discrete AGG, AAG and AGAG meshes. A user-friendly design tool, integrating mesh-optimization into Rhinoceros3D. Innovation in construction through hybrid use of straight elastic AG slats.